ANALISIS PENGARUH PERUBAHAN TUTUPAN LAHAN TERHADAP SUHU PERMUKAAN DI KOTA BANDAR LAMPUNG TAHUN 2013 DAN 2023 - Saputra, Ridho Abdhe; Sekarsih, Fitria Nuraini (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
Over a period of 10 years, there has been an increase in the population in Bandar Lampung City which has caused changes in land cover. As a result, surface temperatures have increased, especially in urban areas. Therefore, this study was conducted to determine the distribution and effect of changes in land cover on surface temperatures. Remote sensing methods were used to calculate the spatial distribution of surface temperatures and to calculate changes in the area of vegetation index values, built-up land indexes, and humidity indexes in Bandar Lampung City in 2013 and 2023. The results showed an increase in surface temperature of 1.92℃. In 2013, the average temperature was 25℃ and increased in 2023 to 26.92℃. Compared to 2013, the temperature distribution area (26-28℃) has expanded by around 8673.39 Ha spread throughout Bandar Lampung City. Based on the results of the coefficient correlation analysis, it is known that the increase in surface temperature is significantly due to changes in land cover, especially by the building index (NDBI), with a determination coefficient (R²) of 0.545 for 2013 and 0.5133 for 2023.